iPEHD: The ifo Prussian Economic History Database - Sascha O. Becker; Francesco Cinnirella; Erik Hornung; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper provides a documentation of the ifo Prussian Economic History Database (iPEHD), a county-level database covering a rich collection of variables for 19th-century Prussia. The Royal Prussian Statistical Office collected these data in several censuses over the years 1816-1901, with much county-level information surviving in archives. These data provide a unique source for micro-regional empirical research in economic history, enabling analyses of the importance of such factors as education, religion, fertility, and many others for Prussian economic development in the 19th century. The service of iPEHD is to provide the data in a digitized and structured way.
Keywords: N13; N33; 330; economic history; Prussia; 19th century; database; county